2013
DOI: 10.1117/12.2021675
|View full text |Cite
|
Sign up to set email alerts
|

Photoemission analysis of chemically modified TlBr surfaces for improved radiation detectors

Abstract: Device-grade TlBr was subjected to various chemical treatments used in room temperature radiation detector fabrication to determine the resulting surface composition and electronic structure. Samples of as polished TlBr were treated separately with 2%Br:MeOH, 10%HF, 10%HCl and 96%SOCl 2 solutions. High-resolution photoemission measurements on the valence band electronic structure and Tl 4f, Br 3d, Cl 2p and S 2p core lines were used to evaluate surface chemistry. Results suggest anion substitution at the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…In the combination of elements detected after Ar etching, the possible chemical states of Tl are Tl 0 , Tl 2 O, Tl 2 O 3 , and TlBr, corresponding to energies of 117.1, 119.1, 118.6, and 119.2 eV, respectively. (13) Since the energy of Tl 0 is close to the measured energy of the subpeak, it was concluded that the subpeak represents Tl 0 . The main Tl 4f peak was considered to be mainly TlBr; thus, we expressed it as Tl (TlBr).…”
Section: Resultsmentioning
confidence: 86%
“…In the combination of elements detected after Ar etching, the possible chemical states of Tl are Tl 0 , Tl 2 O, Tl 2 O 3 , and TlBr, corresponding to energies of 117.1, 119.1, 118.6, and 119.2 eV, respectively. (13) Since the energy of Tl 0 is close to the measured energy of the subpeak, it was concluded that the subpeak represents Tl 0 . The main Tl 4f peak was considered to be mainly TlBr; thus, we expressed it as Tl (TlBr).…”
Section: Resultsmentioning
confidence: 86%